A inserção profissional do egresso do Programa Residência Pedagógica da Universidade Federal de São Paulo (Unifesp) - Conceição, Carla Patrícia Ferreira da (2018)
The present research had as general objective to analyze the pedagogical practice and the challenges encountered by the Pedagogical Residency Program (PRP) egress in the first years of teaching, as well as the contributions of this program to her professional insertion. The study sought to analyze the elements considered by the egress as facilitators or obstructers of the professional insertion; investigate the strategies used to overcome the challenges encountered; and to know, from the point of view of the egress and the management team of the School, the PRP's contributions to the process of professional insertion. It also presents an overview of this Program – from a public institution of Education – and the profile of the egresses corresponding to the period from 2011 to 2014. The literature review includes theorists such as Tardif (2002), Marcelo Garcia (1999), Nóvoa (2009) and Darling-Hammond (2014), among others authors who discuss the beginning of the teaching career, the insertion of teachers and the initial formation. The research was constituted in a case study and had like procedures of data production: observation of the egress’s activities; semi-structured interviews with the egress and the Pedagogical Coordinator of the School; and analysis of documents such as the teacher's logbook, the School's Political Pedagogical Project and the Curricular proposal from Municipal Department of Education of Guarulhos (SP). For the data analysis, the Prose Analysis method (ANDRÉ, 1983) was used, with topics and themes that made it possible to formulate five categories: Professional Insertion; Classroom management; Planning and Evaluation; Initial formation; Pedagogical Residence Program. The main results indicate that the teacher experienced insertion in teaching with few difficulties. The school climate and the participation in the PRP contributed to her professional insertion, mainly in relation to classroom management, planning and evaluation of pedagogical activities